Determinación de los Indices de vegetación normalizada en dos Parroquias Rurales del Canton Latacunga Alaquez y San Buenaventura en el periodo 2016-2017. - Sampedro Garzón, Melany Ivonne (2017)
The project demarcated in the Analysis, conservation and use of biodiversity research line because the determination of the normalized vegetation rates was carried in two rural parishes of Latacunga City such as Alaquez and San Buenaventura establishing a percentage of vegetation using Lansadth 8 images, and the elaboration of thematic maps, where certain pixels underline graphically related to the parameters of the vegetable coverings in the terrestrial surface which is the indicator that has been used in different ambits, from studies related to the dynamics of the ecosystems thereby helping to differentiate crop management base on the knowledge of the existing spectral variability, where graphically determined pixels related to parameters of vegetation cover in the terrestrial agricultural area, as well as to see the great utility of the systems Of geographic information will emphasize. The data captured by all these sensors were digitally stored in the form of tables and maps which generate information that helps the farmer in decision making in the field